A Study of Content and Language Integrated Learning (CLIL) on the Development of English Spelling and Reading Skills of Year 2 EAL Students at Udon Thani International School - Wasoongnoen, Duangtawan; Srisawat, Sasipong (Research Community and Social Development Journal, 2026)
Background and Objective: English serves as an important medium in international schools, particularly for students learning English as an Additional Language (EAL). This research aimed to examine the effects of Content and Language Integrated Learning (CLIL) on the English spelling skills of Grade 2 EAL students at Udon Thani International School by comparing their post-test and pre-test scores, and to investigate students’ satisfaction with the CLIL learning approach. Methodology: Eight Grade 2 EAL students participated in the study selected through purposive sampling. The research instruments designed included Content and Language Integrated Learning (CLIL) based with 8 lesson plans, an English spelling achievement test, and a student satisfaction questionnaire. The instructional intervention was conducted over 4 weeks, totaling 8 hours. Data were analyzed using mean, standard deviation, and a paired-samples t-test to examine differences between post-test and pre-test scores, while descriptive statistics were used to analyze student satisfaction. The instructional activities included vocabulary exposure, guided spelling practice, and interactive learning tasks that encouraged students to use English in meaningful classroom contexts. Results: The results revealed that the English spelling scores of Grades 2 EAL students after learning through the CLIL approach were significantly higher than their scores before the intervention. In addition, the students reported a high level of satisfaction with the learning content, instructional activities, and teacher support provided through the CLIL approach. The improvement suggests that integrating language learning with academic content can support students’ understanding of spelling patterns and promote early literacy development. Discussion and Suggestions: The findings suggest that Content and Language Integrated Learning (CLIL) serve as an instructional approach for developing English spelling skills among primary-level EAL students. Integrating language learning with academic content promotes meaningful learning experiences, increases learner engagement, and supports language development. Contextualized learning activities also help students connect vocabulary knowledge with real learning situations. Therefore, Content and Language Integrated Learning (CLIL) should be encouraged for use in English language instruction at the primary education level. Further research involving larger samples and longer instructional periods is recommended to strengthen the generalizability of the findings.